The implementation of REAP strategy to improve students reading comprehension of analytical expositional text in digital era - Rayani Siregar, Fitri; Sustri Harida, Eka; ., Miranti; Fahmei Lubis, Rayendriani; Linda Vinde Rambe, Sokhira (KnE Social Sciences, 2023)
and Ponder (REAP) strategy using technology to improve analytical exposition text comprehension of the private senior high school students. The research was in an experimental study with pre-test and post-test design. In experimental class consisted of 26 students and in the control class consisted of 26 students as the sample of this research. The data were collected by using reading comprehension test with multiplechoice form and analyzed by using t-test formula. The finding showed that there was a difference mean-score before and after using REAP Strategy. So, by implementing REAP Strategy to students’ analytical exposition text comprehension at grade XI of private senior high school students in Indonesia in digitalization era, the students’ reading comprehension improved. Moreover, it is suggested next researchers, to conduct a deeper exploration in teaching expositional texts using REAP strategy. Keywords: REAP strategy; digital era; senior high school